Beyond the Human Touch: How Instagram Influencers Drive Engagement and Purchase Intentions Among Vietnam’s Digital-Savvy Youth - Lee, Eun-Mi; Mai, Dang Xuan (Journal of Posthumanism, 2025)
Instagram has become a powerful platform for businesses to engage with their target audiences. This study identifies key factors that influence purchase intentions by shaping customer engagement. Using a convenience sample of 216 young Instagram users in Vietnam, data were collected through an online questionnaire. The results indicate that fan bond, enjoyability, and attractiveness positively impact customer engagement, which in turn boosts purchase intentions. However, expertise was found to have no significant effect on customer engagement. This study highlights the importance of effective influencer marketing strategies, focusing on how Instagram influencers impact customer engagement and purchase intentions among young users in Vietnam. Furthermore, by blurring the boundaries between human and digital agency, influencer marketing exemplifies a posthumanist shift in consumer behavior, where online interactions increasingly shape identity and decision-making.